Effects of the ketogenic diet on dentate gyrus and CA3 KCC2 expression in male rats with electrical amygdala kindling-induced seizures - Granados-Rojas, Leticia; Hernández-López, Leonardo; Bahena-Alvarez, Emmanuel Leonardo; Juárez-Zepeda, Tarsila Elizabeth; Custodio, Verónica; Martínez-Galindo, Joyce Graciela; Jerónimo-Cruz, Karina; Tapia-Rodríguez, Miguel; Vanoye-Carlo, America; Duran, Pilar; Rubio, Carmen (Frontiers in Neuroscience, 2025)
IntroductionKetogenic diet (KD), a high-fat, low-carbohydrate, and adequate protein diet, is a non-pharmacological treatment for refractory epilepsy. However, their mechanism of action is not fully understood. The cation-chloride cotransporter, KCC2, transports chloride out of neurons, thus contributing to the intraneuronal concentration of chloride. Modifications in KCC2 expression by KD feeding could explain the beneficial effect of this diet on epilepsy. This study aimed to determine the impact of KD on KCC2 expression in dentate gyrus layers and Cornu Ammonis 3 (CA3) strata of rats with seizures induced by amygdaloid kindling.Materials and methodsMale Sprague Dawley rats were fed a normal diet (ND) or KD from postnatal day 24 until the end of the experiment. At 6 weeks after the start of the diets, rats were subjected to an amygdala kindling epilepsy model, sham or remain intact. Glucose and β-hydroxybutyrate concentrations were quantified. The after-discharge duration (ADD), latency, and duration of stages of kindling were evaluated. In addition, KCC2 expression was evaluated using optical density. A Pearson bivariate correlation was used to determine the relationship between KCC2 expression and ADD.ResultsAt the end of the experiment, the KD-fed groups showed a reduction in glucose and an increase in β-hydroxybutyrate. KD reduced ADD and increased latency and duration of generalized seizures. In ND-fed animals, kindling reduced KCC2 expression in all three layers of the dentate gyrus; however, in KD-fed animals, no changes were observed. KD treatment increased KCC2 expression in the kindling group. In CA3, the pyramidal and lucidum strata showed an increase of KCC2 in KD-fed groups. Besides, the kindling had lower levels of KCC2 than the sham and intact groups. In all layers of the dentate gyrus and pyramidal and lucidum CA3 strata, the correlation indicated that the higher the KCC2 expression, the shorter the ADD during generalized seizures.ConclusionKD reduces ADD in generalized seizures. In addition, KD has a putative neuroprotective effect by preventing the kindling-induced reduction of KCC2 expression in the molecular, granule, and hilar dentate gyrus layers and pyramidal and lucidum CA3 strata. Increased KCC2 expression levels are related to a shorter duration of generalized seizures.